2022
DOI: 10.3389/fmed.2021.800421
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NF-kB in the Downregulation of Organic Cation Transporter 2 Expression and Renal Cation Secretion in Kidney Disease

Abstract: Organic cation transporter 2 (OCT2), encoded by the SLC22A2 gene, is the main cation transporter on the basolateral membrane of proximal tubular cells. OCT2 facilitates the entry step of the vectorial transport of most cations from the peritubular space into the urine. OCT2 downregulation in kidney disease models is apparent, yet not clear from a mechanistic vantage point. The aim of this study was to explore the role of inflammation, a common thread in kidney disease, and NF-kB in OCT2 modulation and tubular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…OCT2 expression in the kidneys is reduced in CKD. Studies with nephrectomized rats have shown a decrease in Oct2 levels in the kidneys [ 85 , 130 ]. However, Ji et al (2002) demonstrated that Oct2 levels were restored in nephrectomized rats with the administration of testosterone, which regulates its expression [ 85 ].…”
Section: Cell Membrane Transporters Of Uremic Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT2 expression in the kidneys is reduced in CKD. Studies with nephrectomized rats have shown a decrease in Oct2 levels in the kidneys [ 85 , 130 ]. However, Ji et al (2002) demonstrated that Oct2 levels were restored in nephrectomized rats with the administration of testosterone, which regulates its expression [ 85 ].…”
Section: Cell Membrane Transporters Of Uremic Toxinsmentioning
confidence: 99%
“…However, Ji et al (2002) demonstrated that Oct2 levels were restored in nephrectomized rats with the administration of testosterone, which regulates its expression [ 85 ]. Recently, Han et al (2022) reported reduced levels of OCT2 in renal biopsies of patients with CKD [ 130 ]. In addition, polymorphisms in OCT2 gene encoding and changes in its expression may also influence the renal clearance via this transporter.…”
Section: Cell Membrane Transporters Of Uremic Toxinsmentioning
confidence: 99%